FAKTOR–FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PELEMBAB WAJAH GARNIER DI KOTA BATAM - Dinawati, Dinawati; Suhardi, Suhardi (LPPM Universitas Putera Batam, 2025)
This study aims to identify and analyze the extent to which Brand Ambassador, brand image, and product quality influence consumer purchasing decisions for Garnier facial moisturizer products in Batam City. The increasingly competitive beauty industry demands companies to implement effective marketing strategies, including the use of public figures, brand identity reinforcement, and the provision of high-quality products. A quantitative approach with a survey method was used in this research. Data were collected through questionnaires distributed to 100 respondents who are Garnier product users in Bengkong District, Batam City. The data were analyzed using multiple linear regression to determine the influence of the independent variables on the dependent variable. The results indicate that brand image and product quality have a significant impact on purchasing decisions, while Brand Ambassador does not show a significant effect. These findings suggest that although a brand ambassador may add promotional value, the primary factors influencing purchasing decisions are consumers' positive perception of the brand and their satisfaction with product quality. Therefore, it is recommended that companies focus more on enhancing product quality and strengthening brand image to maintain and expand market share. Keywords: Brand Ambassador; Brand Image; Product Quality; Purchasing Decision; Garnier.